Development of Design Rules for Composite Construction - Viest, Ivan M. (Engineering Journal, 2003)
Historical development of the requirements for the design of composite structures made up of steel elements and concrete, as practiced in the United States, is reviewed. Included are buildings and highway bridges. After a brief description of the origins of composite construction in America, an emphasis is placed on early design rules issued by the American Institute of Steel Construction (AISC), American Association of State Highway Transportation Officials (AASHTO), the Joint Committee on Concrete and Reinforced Concrete, and the American Concrete Institute (ACI). The discussion is divided into two parts. The first, dealing with composite beams, traces the development of the AISC and AASHTO requirements; it also includes remarks on the strength of stud shear connectors placed in the trough of a steel deck. AISC, Joint Committee and ACI provisions for composite columns are the subject of the second part of the discussion. Extensive practical experience has demonstrated that composite construction is a system suitable for areas of high seismicity. It has been used in Japan for decades but on the west coast of the United States its use spread only relatively recently. The first U.S. seismic provisions for composite construction were included in the 1994 version of the National Earthquake Hazards Reduction Program's Recommended Provisions for Seismic Regulations for New Buildings issued by the Federal Emergency Management Agency in 1994. AISC included composite construction in the 1997 Seismic Provisions for Structural Steel Buildings and the provisions were also included by reference in the 2000 edition of the International Building Code.